Work in Black and White : Striving for the American Dream - Branch, Enobong Hannah, 1983-; Hanley, Caroline (Book collections on Project MUSE., 2022)
"Black and White Americans have responded to increasing economic insecurity in very different ways, reconciling their economic realities within distinctly racialized conceptions of meritocracy and the American dream. Americans in all racial groups often put faith in education as the key to upward mobility. But as education provides less and less job and financial security, Black and White men and women are forced to navigate a contradictory ideological constellation where education is still seen as the great equalizer and lynchpin of equal opportunity but where evidence shows that education does not ultimately ameliorate the inequalities they are trying to overcome. For historical reasons, Black and White workers respond to the levels of insecurity in their lives in ways that diverge according to their racial group, and the rise of insecure work has also changed the way Black and White men and women draw on conceptions of race and gender-their own, others'-to make sense of who deserves security. This book highlights the divergence in the narratives that Black and White Americans use to explain their misfortunes and those of others, because the stories people tell matter. By shining a light on the way these stories have influenced people's responses to their struggles, this book offers a possibility for change. It shows that the way people interpret insecurity, inequality, and uncertainty is not merely due to economic misfortune but the result of political choices in the face of the legacies of historical inequality"--